1990
DOI: 10.1073/pnas.87.15.5710
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of fibroblast growth factors in human gliomas and meningiomas: demonstration of cellular source of basic fibroblast growth factor mRNA and peptide in tumor tissues.

Abstract: The growth autonomy of human tumor cells is considered due to the endogenous production of growth factors. Transcriptional expression of candidates for autocrine stimulatory factors such as basic fibroblast growth factor (FGF), acidic FGF, and transforming growth factor type (3 were determined in human brain tumors. Basic FGF was expressed abundantly in 17 of 18 gliomas, 20 of 22 meningiomas, and 0 of 5 metastatic brain tumors. Northern Blot Analysis. Total RNA was isolated by the guanidinium thiocyanate/cesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
3

Year Published

1991
1991
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(104 citation statements)
references
References 24 publications
4
97
0
3
Order By: Relevance
“…This lesion was sufficiently large to obtain numerous sections for immunohistochemical staining for other gene products. Similar to what has been reported for high-grade human gliomas (Takahashi et al 1990;Plate et al 1994), cells in the implicated region overexpress endogenous bFGF and vascular endothelial growth factor (VEGF). The cells comprising this lesion also stain with antibodies to GFAP and nestin, indicating an immature astrocytic cell type.…”
Section: Features Of Gliomas Are Induced By Egfr* Gene Transfer In Insupporting
confidence: 50%
“…This lesion was sufficiently large to obtain numerous sections for immunohistochemical staining for other gene products. Similar to what has been reported for high-grade human gliomas (Takahashi et al 1990;Plate et al 1994), cells in the implicated region overexpress endogenous bFGF and vascular endothelial growth factor (VEGF). The cells comprising this lesion also stain with antibodies to GFAP and nestin, indicating an immature astrocytic cell type.…”
Section: Features Of Gliomas Are Induced By Egfr* Gene Transfer In Insupporting
confidence: 50%
“…Schweigerer et al (1987b) reported that basic FGF is an autocrine growth factor for human embryonal rhabdomyosarcoma cells. In addition, human gastric cancers, gliomas, meningiomas and renal cell carcinomas have been reported to express basic FGF mRNA (Takahashi et al, 1990;Zagzag et al, 1990;Tanimoto et al, 1991;Eguchi et al, 1992), and Kaposi's sarcoma cells have been reported to release basic FGF into their medium (Ensoli et al, 1989). However, basic FGF lacks a typical signal peptide region which facilitates secretion (Gospodarowicz et al, 1987) and its release mechanism remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Basic FGF is thought to induce fibrosis, angiogenesis, and tumour progression in human gastric carcinomas, renal cell carcinomas, brain tumours, and malignant melanoma through an autocrine mechanism (Becker et al, 1989;Takahashi et al, 1990;Zagzag et al, 1990;Tanimoto et al, 1991;Eguchi et al, 1992). Pancreatic carcinomas exhibit strong stromal reactions, or desmoplasia, and have an aggressive behaviour and poor prognosis .…”
mentioning
confidence: 99%
“…Overexpression of FGF-2 in certain gliomas correlates with the grade of the tumor and the extent of anaplasia (Zagzag et al, 1990). Proliferation of glioma cells is inhibited by FGF-2-speci®c antisense oligonucleotides (Liberman et al, 1987;Takahashi et al, 1990;Morrison, 1991;Morrison et al, 1994a).…”
Section: Introductionmentioning
confidence: 99%